Affected Territory and Objects of the North Caucasus by Lightning - A. A. Adjieva; Z. M. Kerefova; R. A. Gyatov (Наука. Инновации. Технологии, 2022)
Introduction: a thunderstorm is a complex atmospheric phenomenon. The main signs of this phenomenon are multiple electrical discharges between differently charged regions of the cloud - cloud discharges, different clouds-inter-cloud discharges, or between clouds and the ground -ground discharges. Materials and methods of the research: the results of instrumental studies of thunderstorm activity and measurements of lightning discharge parameters were used to analyze the features of climatic characteristics of thunderstorms and assess the incidence of lightning on the territory and objects of the North Caucasus. The results of the study and their discussion: an experimental and theoretical study of the physical and statistical characteristics of thunderstorm activity and the damage to the territory and objects by lightning, typical for the South of the European part of Russia, was performed. Conclusions: a map of the average annual lightning strike rate in the North Caucasus is constructed. The map is based on instrumental observations about the number of days with thunderstorms and the earth's susceptibility.